Prognostic impact of complex karyotype on post‐transplant outcomes of myelofibrosis. Issue 5 (19th August 2022) - Okada, Yosuke; Takenaka, Katsuto; Murata, Makoto; Shimazu, Yutaka; Tachibana, Takayoshi; Ozawa, Yukiyasu; Uchida, Naoyuki; Wakayama, Toshio; Doki, Noriko; Sugio, Yasuhiro; Tanaka, Masatsugu; Masuko, Masayoshi; et al.
Abstract: Chromosomal abnormalities in the role of prognostic factor for transplant patients with myelofibrosis (MF) are not fully investigated. Regarding complex karyotype (CK), we retrospectively analyzed 241 patients with primary and secondary MF who received a first allogeneic hematopoietic cell transplantation (HCT). Based on an unfavorable karyotype in the Dynamic International Prognostic Scoring System, we compared the outcomes in 3 groups: favorable karyotype, unfavorable karyotype including CK (unfavorable‐CK(+)), and unfavorable karyotype not including CK (unfavorable‐CK(–)). Overall survival was significantly shorter in the unfavorable‐CK(+) group (hazard ratio (HR) 2.49, 95% CI: 1.46–4.24, P < 0.001), whereas there was no difference between the unfavorable‐CK(–) group and the favorable group (HR 0.57, 95% CI: 0.20–1.59, P = 0.28). In addition, a significantly higher proportion of patients in the unfavorable‐CK(+) group did not achieve complete remission after HCT ( P = 0.007). The cumulative incidence of disease progression was significantly higher in the unfavorable‐CK(+) group (HR 2.5, 95% CI 1.6–3.92, P < 0.001), whereas that in the unfavorable‐CK(–) group was comparable to that in the favorable group (HR 0.49, 95% CI 0.12–1.94, P = 0.31). Further investigations will be needed to clarify the impact of CK on transplant outcomes in MF.